1963
DOI: 10.1139/b63-126
|View full text |Cite
|
Sign up to set email alerts
|

A New Genus of the Gymnoascaceae With Swollen Peridial Septa

Abstract: A new genus of the Gymnoascaceae, Auxarthron, is established to include certain species previously excluded from Gymnoascus and Myxolrichum. The genus is characterized by the presence of (1) enlargements at the septa in the peridial hyphae; (2) ascospores globose, subglobose to ovoid, asperulate to echinulate-reticulate, and hyaline to pale orange-yellow-brown; (3) the presence of either short spines or elongate appendages, or both; (4) lightly colored, elongate appendages which are non-septate except for one,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…The species is of widespread occurrence and has been previously reported from Denmark as Myxotrichum brunneum (Rostrup 1895, Orr & Kuehn 1971, Apinis 1964). Orr et al (1963) reported this fungus from a mycotic toenail.…”
Section: 3mentioning
confidence: 99%
“…The species is of widespread occurrence and has been previously reported from Denmark as Myxotrichum brunneum (Rostrup 1895, Orr & Kuehn 1971, Apinis 1964). Orr et al (1963) reported this fungus from a mycotic toenail.…”
Section: 3mentioning
confidence: 99%
“…This latter character has not been observed by us in accepted species of Gymnoascaceae and we have excluded several species possessing this character from the family and have placed them in the Eurotiaceae; viz., Arachniotus indicus Chattopadhyay & Das Gupta (10); A. trisporus Hotson (13); A. trachyspermus Shear (14); Gymnoascus luteus (Zukal) Sacc. and G. flaus Klocker (22). Arachniotus trisporus proved to be a synonym for Byssochlamys nivea Westling.…”
mentioning
confidence: 92%
“…Gymnoascus verticillatus Smith was excluded from the genus Gymnoascus because it failed to conform to the characteristics of that genus as described by Orr et al (22). Orr and Kuehn (24) redescribed the fungus as Actinodendron verticillatum (Smith) Orr & Kuehn based on observations of the original and later material.…”
mentioning
confidence: 99%
“…Castan-edomyces is another genus of Onygenales that forms elongate appendages, but differs in having a membranous peridium similar to that in Aphanoascus . The generic name Auxarthron was established by Orr et al (1963) for species with “enlargements at the septa in the peridial hyphae; lightly coloured, elongate appendages which are non-septate except for one, two or three basal septa with characteristic swellings at such septa”. The generic name means ‘swollen joints’, and the genus now comprises 13 species (Sole et al .…”
Section: Introductionmentioning
confidence: 99%